ROLE OF SINGLE NUCLEOTIDE GENE POLYMORPHISMS IN THE DEVELOPMENT OF ULCERATIVE COLITIS - Kyrian, O.A.; Dorofeyev, A.E.; Khaymenova, G.S.; Dorofeyeva, A.A. (World of Medicine and Biology, 2020)
The purpose of the work was to study the features of the IL1 (T-31C), IL1 (T-511C), IL6 (C-174 G), IL10 (592C> A), IL10 (C-819T), IL10 (G- 1082A), Tlr2 (Thr399ile), Tlr4 (Thr399ile), Tlr4 (Asp299Gly) genes polymorphic variants influence on the development of ulcerative colitis in patients. The total of 53 patients with ulcerative colitis were examined, the control group included a random sample of 49 healthy persons. Association of the ulcerative colitis development with the incidence of single nucleotide polymorphism of IL10 wild genotype gene (rs1800896), homozygous G/G genotype of single nucleotide polymorphism of the Tlr4 gene (rs4986790), the frequency of the T allele in the IL1 gene (rs1143627), C allele in the IL1 gene (rs 16944) and IL10 (rs1800872), which contributed to the disturbance and imbalance in the production of pleiotropic cytokines IL1 and IL10, predisposing to the development of ulcerative colitis and aggravating the course of the disease. The work shows associative links for single nucleotide polymorphism of Tlr4 gene (rs4986791) with the development of nonspecific ulcerative colitis both according to the multiplicative model with the C allele and according to the general inheritance model with the wild type of C/C genotype, which confirms the importance of this single nucleotide polymorphism in the development of the disease.